Strategy of Melati II Tourism Village, Perbaungan District in Increasing Tourist Visits in Serdang Bedagai Regency - Siregar, Titin Agustina; Humaizi, Humaizi; Irfan, Irfan (Universitas Medan Area, 2025)
This article aims to analyze the strategies carried out by the village government and tourism office, as well as the role of actors in increasing tourist visits to Melati II Village. The research problem focuses on efforts to optimize local tourism potential to attract tourists. To overcome this problem, theoretical references are used as the basis for analysis. Data were collected through observation, interviews, and document analysis, then analyzed qualitatively using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the village government utilizes local potential by organizing cultural attractions such as Kuda Kepang, developing Kebun Jeruk Petik Sendiri and Palungguhan To Joyo, and increasing the accessibility of tourist locations despite budget constraints. The Serdang Bedagai Regency Tourism Office supports tourism promotion and development through training and innovation of unique attractions. In addition, actors such as village officials, local business actors, the community, and tourists collaborate in maintaining the environment, improving service quality, and promoting the village through social media. This study concludes that collaboration between the government, community, and tourists can make Melati II Village a leading tourist destination.